(untitled) (Washington, D.C, 1998)
This book consists of the following many parts such as growth anf China's environmental, pollution, health, and productivity estimating today's costs, plotting alternative futures.
Keywords: Air pollution,Environmental engineering,Environmental protection,Water pollution